China Rising in Latin America - K. O. Volkov (Ибероамериканские тетради, 2015)
The article analyses one of the most important international relations trends in Latin America in the early 21st century, the PRC’s growing presence in Latin America. The first part of the article deals with the historical background of the phenomenon, pragmatic interests of the parties and China’s skillful diplomacy with the second one concentrating on the comparative analysis of models of bilateral relations between China and the leading nations of the region.